A novel ultrasound predictor of pulmonary capillary wedge pressure assessed by the combination of left atrial volume and function: A speckle tracking echocardiography study. Issue 3 (September 2015) - Kawasaki, Masanori; Tanaka, Ryuhei; Ono, Koji; Minatoguchi, Shingo; Watanabe, Takatomo; Iwama, Makoto; Hirose, Takeshi; Arai, Masazumi; Noda, Toshiyuki; Watanabe, Sachiro; Zile, Michael R.; Minatoguchi, Shinya
Abstract Background We hypothesized that a development of a novel index based on the combination of left atrial volume (LAV) and left atrial (LA) function evaluated by the time–LA volume curve using speckle tracking echocardiography (STE) would be accurate and useful to estimate pulmonary capillary wedge pressure (PCWP). Our goal was to develop a novel index of PCWP based on a combination of LAV and LA function using STE. Methods A cross-validation study was performed with the patients divided into a training study to define the novel index (n = 50) and a testing study to validate the index (n = 196). PCWP was measured by right heart catheterization, and phasic LAV and emptying function (EF) were measured by STE. Results Simple linear regression analysis in the training study revealed that the novel index that best estimated PCWP was the kinetics-tracking index [KT index = log10 (active LAEF/minimum LAV index)]. Multiple regression analysis revealed that the KT index was the most reliable predictor of PCWP. It had the strongest correlation with PCWP (r = −0.86, p < 0.001) among all echocardiographic parameters. In the testing study, PCWP estimated by the KT index was also strongly correlated with measured PCWP (r = 0.92, p < 0.001). These correlations were also strong in the patients with reduced left ventricular ejection fraction (<50%), chronic heart failure, and chronic atrial fibrillation (r = 0.92, r = 0.91, r = 0.79, p < 0.001, respectively). Conclusions A novel index (KT index) using a combination of LAV and LA function was a powerful and useful predictor of PCWP and may be valuable in routine clinical practice.